A Brief Study of Certain Class of Harmonic Functions of Bazilevič Type. (8th September 2013) - Oladipo, A. T.; Breaz, D.
Abstract : We define and investigate a new subclass of Bazilevič type harmonic univalent functions using a linear operator. We investigated the harmonic structures in terms of its coefficient conditions, extreme points, distortion bounds, convolution, and convex combination. So, also, we discussed the subordination properties for the functions in this class.